The Effect of the Lee Silverman Voice Treatment (LSVT) BIG Method Based on Occupation on Older Adult Functional Mobility Balance - Luthfi, Muhammad; Idalasari, Kharisma Nur (UI Scholars Hub, 2026)
Balance impairment is one of the major problems commonly experienced by older adults as a result of degenerative processes, leading to an increased risk of falls. Falls may cause fear of recurrent falling, reduced physical activity, loss of physical capability, and may eventually result in disability and psychological consequences such as depression. Structured, occupation-based physical activity has been shown to provide various benefits for older adults, including improving physical function, slowing functional decline associated with degenerative processes, reducing fall risk, and enhancing postural control. This study aimed to analyze the effect of the occupation-based Lee Silverman Voice Treatment (LSVT) BIG method on functional balance in older adults. A quantitative approach with a pre-experimental pretest–posttest design was employed. A total of 10 participants were recruited using a total sampling technique and underwent 16 intervention sessions over a 4-week period, with each session lasting 60 minutes. Measurement instruments included a respondent characteristic questionnaire, the Berg Balance Scale as the primary outcome measure, and the Canadian Occupational Performance Measure (COPM) for intervention planning. The results indicated that individual factors (age, Body Mass Index, and comorbidities), as well as physical activity characteristics (frequency, intensity, and duration of exercise), were not significantly associated with functional balance in this sample (p > 0.05). In contrast, the paired t-test analysis demonstrated a significant effect of the occupation-based LSVT BIG intervention on functional balance in older adults (p < 0.001). These findings suggest that the occupation-based LSVT BIG method may be considered a promising intervention approach for improving functional balance in older adults